Analytical and simulation results of micro-ring resonator system using two eyes imaging model - Tanaram, C.; Phatharacorn, P.; Chiangga, S.; Yupapin, P. P. (International Journal of Scientific World, 2015)
In this review article, the artificial vision model using the 3 cascaded conjugate mirrors system can be constructed, analyzed and simulated. A single 3D pixel (point) imaging construction is formed and obtained by using the conjugate mirror concept, where the large area of pixels can be potentially constructed and realized for large area application. This is a simulation work, where the software program is the finite difference time domain (FDTD) commercial program (Opti-wave). However, the used device parameters and materials can be fabricated and formed the artificial eyes for 3D artificial vision. Simulation result obtained has shown that the whispering gallery modes (WGMs) of radiation within the cascaded microring conjugate mirrors can be easily formed, and are coupled by the two nonlinear side rings, which can be potentially used for 3D imaging pixel construction applications by the two eyes construction model.